An Analysis of Factors Affecting Utilisation of Moodle Learning Management System by Open and Distance Learning Students at the University of Eswatini - Eunice, Mthethwa-Kunene, Khetsiwe; Cosmas, Maphosa (American Journal of Social Sciences and Humanities, 2019)
The use of technology in teaching and learning for students in Open and Distance Learning (ODL) is important in bridging the gap between the student, the lecturer and the content. Furthermore, technology enhances communication between staff and students and among students to improve the quality of learning experiences. The study sought to establish institutional and personal factors promoting or hindering ODL students’ utilisation of the Moodle Learning Management System at the University of Eswatini. A concurrent triangulation design located in the pragmatic research paradigm combining the quantitative and qualitative research approaches was utilised in the study. One hundred and ninety-eight (198) students studying different programmes offered through ODL responded to a questionnaire. The semi-structured questionnaire was administered to a stratified random sample of ODL students at different levels of study in the university. Quantitative data were analysed using the SPSS software and reported in descriptive statistics. The identified factors were correlated with students’ usage of the LMS to assess whether there was any relationship. Thematic analysis was used to analyse qualitative data. The study found that ODL students’ perceived usefulness and ease of use, trust and satisfaction affected their usage of Moodle albeit there was weak to moderate positive relationships. Qualitative data on challenges experienced by students in using Moodle unearthed institutional factors such as inadequate technological infrastructure and insufficient student training and support. The study recommends improvement of the institutional internet bandwidth soon as well as continuous training and support for both students and course instructors.